Effect of a high strength chemical industry wastewater on microbial community dynamics and mesophilic methane generation - Venkatakrishnan, Harish (2014)
A high strength chemical industry wastewater was assessed for its impact on anaerobic microbial community dynamics and consequently mesophilic methane generation. Cumulative methane production was 251 mL/g total chemical oxygen demand removed at standard temperature and pressure at the end of 30 days experimental period with a highest recorded methane percentage of 80.6% of total biogas volume. Volatile fatty acids (VFAs) analysis revealed that acetic acid was the major intermediate VFAs produced with propionic acid accumulating over the experimental period. Quantitative analysis of microbial communities in the test and control groups with quantitative real time polymerase chain reaction highlighted that in the test group, Eubacteria (96.3%) was dominant in comparison with methanogens (3.7%). The latter were dominated by Methanomicrobiales and Methanobacteriales while Methanosarcinaceae in test groups increased over the experimental period, reaching a maximum on day 30. Denaturing gradient gel electrophoresis profile was performed, targeting the 16S rRNA gene of Eubacteria and Archaea, with the DNA samples extracted at 3 different time points from the test groups. A phylogenetic tree was constructed for the sequences using the neighborhood joining method. The analysis revealed that the presence of organisms resembling Syntrophomonadaceae could have contributed to increased production of acetic and propionic acid intermediates while decrease of organisms resembling Pelotomaculum sp. could have most likely contributed to accumulation of propionic acid. This study suggested that the degradation of organic components within the high strength industrial wastewater is closely linked with the activity of certain niche microbial communities within eubacteria and methanogens.